A gender performance indicator for irrigation: concepts, tools and applications - van Koppen, Barbara (International Water Management Institute, 2002)
Although gender issues are today a priority on the agendas of irrigation policy makers, interventionists, farm leaders and researchers, there is still a considerable gap between positive intentions and concrete action. An important but hitherto ignored reason for this is the lack of adequate generic concepts and tools that are policy-relevant and can accommodate the vast variation in irrigation contexts worldwide. The Gender Performance Indicator for Irrigation (GPII) aims to fill this gap. In any particular scheme, this tool diagnoses the gendered organization of farming and gender-based inclusion or exclusion in irrigation institutions. It informs irrigation agencies what they themselves can do for effective change-if necessary. The tool also identifies gender issues beyond a strict mandate of irrigation water provision. The Indicator was applied and tested in nine case studies in Africa and Asia. The research report presents the underlying concepts, methodological guidelines and selected applications of the GPII.